Multitude: Cross-Cultural Readings for Writers - Divakaruni, Chitra B. (New York McGraw-Hill, Inc., 1993)
Intended for use in the first-year college composition classes, Multitude is a thematically arranged collection of readings with a multicultural focus that simulates our mosaic-like society, broadens our awareness of diversity, and allows us to take pride in our many heritages.
Keywords: Reading